Venous stroke–a stroke subtype that should not be ignored - Zhou, Yifan; Jiang, Huimin; Wei, Huimin; Liu, Lu; Zhou, Chen; Ji, Xunming (Frontiers in Neurology, 2022)
Globally, stroke ranks second among the leading causes of death. Stroke is caused not only by arterial occlusion but also by cerebral venous thrombosis. Therefore, stroke includes arterial stroke and venous stroke. Arterial stroke is currently the main subtype of stroke, and research on this type has gradually improved. Venous stroke, the other type, accounts for 0.5%-1% of all strokes. Due to the lack of a full understanding of venous stroke, as well as its diverse clinical manifestations and neuroimaging features, there are often delays in admission for it, and it is easy to misdiagnose. The purpose of this study was to review the pathophysiology mechanisms and clinical features of arterial and venous stroke and to provide guidance for further research on the pathophysiological mechanism, clinical diagnosis, and treatment of venous stroke. This review summarizes the pathophysiological mechanisms, etiology, epidemiology, symptomatology, diagnosis, and treatment heterogeneity of venous stroke and compares it with arterial stroke. The aim is to provide a reference for a comprehensive understanding of venous stroke and a scientific understanding of various pathophysiological mechanisms and clinical features related to venous stroke, which will contribute to understanding the pathogenesis of intravenous stroke and provide insight into diagnosis, treatment, and prevention.